Synthesis and Investigation of Visible-Light-Activated Rutile Phase Modified TiO2 - Behjou, A.; Aghaie, H.; Zare, K.; Aghaie, M. (Asian Journal of Chemistry, 2012)
Nitrogen-containing dye-sensitizers loading on TiO2 has decreased the electron excitation energy and therefore has improved the photocatalytic performance by increasing the sensitivity under visible light irradiation. The addition of metal cations such as platinum on TiO2 via the intermediation role for moving the conduction band electron to electron acceptors and increasing the pair electron-holes long-life has increased the photocatalytic reaction rate and has improved the photocatalytic activity. In this study, at first titanium isopropoxide precursore has been used by the sol-gel method for TiO2 synthesizing. Then, the effect of calcination temperatures in forming of the nanosize photocatalyst was studied. In addition, their phases were studied with XRD test and analyzed their specific surface area using the BET test. Finally, the ability of the absorption of visible light by all of samples was investigated by means of diffuse reflectance spectra and has been compared with commercial TiO2-P25 (consist of 80 % anataze phase and 20 % rutile phase).